Equalization of energy density in boiling water reactors (as exemplified by WB-50). Development and testing of WB -50 computational model on the basis of MCU-RR code; Journal of Physics: Conference Series; Vol. 781 : Nuclear Reactor Physics 2016 (ICNRP-2016) - Chertkov Yu. B. Yuri Borisovich; Disyuk V. V. Valentin Vladimirovich; Pimenov E. Yu. Eduard Yurjevich; Aksenova N. V. Nataliya Valerievna (2017, 2017)
Title screen